PENYESUAIN DIRI PADA REMAJA YANG MENJADI IBU - MIRA ARIYANI; FADHILAH KAMILIA (Journal of Research and Measurement in Psychology, 2015)
This research aims to see the adolescent maternal adjustment (teenage mother). Methods of data collection in this study used interview method. The subjects of this study were three people and analyzed using Interpretative Phenomenological Analysis (IPA) method. The problems on teenage mother is financial problems, still dependent on their parents, drop out and not work. The results of this study show that three subjects have been able and unable to adjustment to their partner, some are able and unable to sexual adjust with their spouses, have problems with financial adjustment, some are able and unable to adjust to the couple's family.